Creating Sustainable Communities Lessons from the Hudson River Region - Scarce, Rik (State University of New York Press, 2015)
From Mount Marcy to Manhattan and beyond, the Hudson River region has become an incubator for rich and varied experiments in sustainable living. In this fascinating book, Rik Scarce showcases some of these efforts by telling the stories of dynamic individuals and organizations that are remaking the region's landscape through ecosystem stewardship, nurturing agricultural practices, and urban renewal for the twenty-first century, along with those promoting creative land-use planning, richly functioning communities, and green businesses. Together, their achievements point to the potential for other areas of the country to forge sustainable futures, and also remind us of the sobering realities and daunting challenges that await us as we attempt to remake our relationships with the planet and with each other.